2010
DOI: 10.1186/1471-244x-10-81
|View full text |Cite
|
Sign up to set email alerts
|

Change in quality of life and their predictors in the long-term follow-up after group cognitive behavioral therapy for social anxiety disorder: a prospective cohort study

Abstract: BackgroundSocial anxiety disorder (SAD) is one of the most common anxiety disorders. The efficacy of cognitive behaviour therapy (CBT) has been examined but to date its effects on Quality of Life (QoL) have not been appropriately evaluated especially in the long term.The study aimed to examine, in the long term, what aspects of Quality of Life (QoL) changed among social anxiety disorder (SAD) patients treated with group cognitive behaviour therapy (CBT) and what predictors at baseline were associated with QoL.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 37 publications
(50 reference statements)
2
29
4
Order By: Relevance
“…The Cohen's d ESs seen in the CCT group in the present study (Table 2) were similar or slightly larger than those found in the aforementioned study. 12 However, TBTR had large to very large ESs at post-treatment in the mental health (ES = 1.09) and social functioning (ES = 1.41) domains, as well as large ESs in the social functioning domains (ES = 0.76) at follow-up, and these results were not accomplished neither in the CCT contrast group of our study nor in that study. 12 A possible explanation for this finding is that TBTR had a more significant effect on fear of negative evaluation (FNE) scores than CCT techniques, as shown in a previous publication of this study.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…The Cohen's d ESs seen in the CCT group in the present study (Table 2) were similar or slightly larger than those found in the aforementioned study. 12 However, TBTR had large to very large ESs at post-treatment in the mental health (ES = 1.09) and social functioning (ES = 1.41) domains, as well as large ESs in the social functioning domains (ES = 0.76) at follow-up, and these results were not accomplished neither in the CCT contrast group of our study nor in that study. 12 A possible explanation for this finding is that TBTR had a more significant effect on fear of negative evaluation (FNE) scores than CCT techniques, as shown in a previous publication of this study.…”
Section: Discussioncontrasting
confidence: 75%
“…12 However, TBTR had large to very large ESs at post-treatment in the mental health (ES = 1.09) and social functioning (ES = 1.41) domains, as well as large ESs in the social functioning domains (ES = 0.76) at follow-up, and these results were not accomplished neither in the CCT contrast group of our study nor in that study. 12 A possible explanation for this finding is that TBTR had a more significant effect on fear of negative evaluation (FNE) scores than CCT techniques, as shown in a previous publication of this study. 16 The one-way ANCOVA showed a significant treatment effect (F[1, 33] = 5.47; p = 0.03) at midtreatment and at post-treatment, with participants in the TBTR group scoring lower on FNE assessments than participants in the CCT group.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Fortunately, there are several efficacious treatments for SAD. Cognitive behavior therapy (CBT) is the most studied psychotherapy for SAD; several studies have demonstrated its efficacy both in the short term and long term [84], with moderate-tolarge effect sizes at post-treatment compared with control conditions [85]. Evidence also supports the use of cognitive therapy (CT) [86] and internet-delivered CBT for SAD [87].…”
Section: Is Sad Undertreated?mentioning
confidence: 99%